Podstawowe zagadnienia polskiej pedagogiki społecznej u progu procesu dyscyplinaryzacji - Żukiewicz, Arkadiusz (Studia Edukacyjne, 2018)
The article presents the basic issues of social pedagogy presented by Helena Radlińska in 1908 during a meeting at the Krakow Circle of Teachers of Higher Schools in Krakow. In her talk, she presented issues of education and social development in a wider historical background. She made reference to international and national experiences. In the conclusion of her speech, she called for the dissemination and socialization of upbringing and social assistance for the poorest social groups.